Controlling Fano resonances in multilayer dielectric gratings towards optical bistable devices. Issue 1 (December 2018) - Hoang, Thu; Ngo, Quang; Vu, Dinh; Nguyen, Hieu
Abstract The spectral properties of Fano resonance generated in multilayer dielectric gratings (MDGs) are reported and numerically investigated in this paper. We examine the MDG consisting of numerous identically alternative chalcogenide glass (As2 S3 ) and silica (SiO2 ) multilayers with several grating widths inscribed through the structure, emphasizing quality (Q ) and asymmetric (q ) factors. Manipulation of Fano lineshape and its linear characteristics can be achieved by tailoring the layers' amount and grating widths so that the proposed structure can be applicable for several optical applications. Moreover, we demonstrate the switching/bistability behaviors of the MDG at Fano resonance which provide a significant switching intensity reduction compared to the established Lorentzian resonant structures.